Biofabrication of synthetic human liver tissue with advanced programmable functions - Rodrigo M. Florentino; Kazutoyo Morita; Nils Haep; Takashi Motomura; Ricardo Diaz-Aragon; Lanuza A.P. Faccioli; Alexandra Collin de l’Hortet; Zeliha Cetin; Carla Frau; Lawrence Vernetti; Anna-Klara Amler; Alexander Thomas; et al. (iScience, 2022)
Summary: Advances in cellular engineering, as well as gene, and cell therapy, may be used to produce human tissues with programmable genetically enhanced functions designed to model and/or treat specific diseases. Fabrication of synthetic human liver tissue with these programmable functions has not been described. By generating human iPSCs with target gene expression controlled by a guide RNA-directed CRISPR-Cas9 synergistic-activation-mediator, we produced synthetic human liver tissues with programmable functions. Such iPSCs were guide-RNA-treated to enhance expression of the clinically relevant CYP3A4 and UGT1A1 genes, and after hepatocyte-directed differentiation, cells demonstrated enhanced functions compared to those found in primary human hepatocytes. We then generated human liver tissue with these synthetic human iPSC-derived hepatocytes (iHeps) and other non-parenchymal cells demonstrating advanced programmable functions. Fabrication of synthetic human liver tissue with modifiable functional genetic programs may be a useful tool for drug discovery, investigating biology, and potentially creating bioengineered organs with specialized functions.